2013
DOI: 10.1002/jbio.201200204
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐operative ex vivo photoacoustic nodal staging in a rat model using a clinical superparamagnetic iron oxide nanoparticle dispersion

Abstract: The ability to accurately detect tumor metastases in lymph nodes is essential for intra-operative staging of various malignancies. Histopathological assessment of nodes has the drawback of a time delay before results are available to the surgeon and a likelihood of missing metastases. Photoacoustic (PA) imaging has been shown to possess the potential to detect melanoma metastases in resected in toto lymph nodes based on intrinsic contrast. To extend application of the method to other malignancies, extrinsic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…157 In recent studies, the potentials of SPIO as PAT contrast agent were investigated for nodal staging. 158,159 Lymph nodes in tumor environment usually exhibit responsive lymphadenopathy which could be mimicked by Incomplete Freund adjuvant (IFA) injection. 160 Thus, 0.1 mL IFA (consisting of water in oil emulsion) was injected on both hind footpads to create induced lymph node swelling.…”
Section: Metallic Nanoparticles As Photoacoustic Tomography Contrasmentioning
confidence: 99%
“…157 In recent studies, the potentials of SPIO as PAT contrast agent were investigated for nodal staging. 158,159 Lymph nodes in tumor environment usually exhibit responsive lymphadenopathy which could be mimicked by Incomplete Freund adjuvant (IFA) injection. 160 Thus, 0.1 mL IFA (consisting of water in oil emulsion) was injected on both hind footpads to create induced lymph node swelling.…”
Section: Metallic Nanoparticles As Photoacoustic Tomography Contrasmentioning
confidence: 99%
“…Grootendorst et al have shown in healthy rats that superparamagnetic iron oxide nanoparticles (Endorem(®)) can be used as a photoacoustic imaging agent for lymph node visualization (87). More recently, they have shown promising results using the same nanoparticles in an ex vivo intraoperative setting in a metastatic prostate cancer model in rats (181). …”
Section: Clinical Applicationsmentioning
confidence: 99%
“…14A). 191 Carbon nanoparticles, 192 copper sulfide nanoparticles (CuS NPs), 18,193,194 nano-graphene, 195 iron oxide NPs, 196 or even QDs 197 have also been successfully used as PA contrast agents. 185 Except for these endogenous optical absorbers, the emergence of exogenous contrast agents accelerated PA imaging applications in signal sensing, functional imaging, biomarker labeling and therapy monitoring greatly.…”
Section: Activatable Photoacoustic Imaging Probesmentioning
confidence: 99%